(3MGTjI Ydi TQM LZejfjs - (3GdHQLfOj, YHO GdYdj Hf eMeO Hf MSjf, HYO (B935 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdeTGQb hGdeZGQH eRjf GdSeGA HGdchGcH agPg JYdjbGJ Ydi GdehGVY GdeTcdI hJfHjgGJ Ydi QehR GdeHGMK GdNajIGdeYVdI ef TQM GdedNU aj GdgjFI GdfShH Edi aGVd GdCFeI bGVj RGOI s
(3BNQgG (B:s
(3deG Hjf aj ehVYg ef Cf GGdcQI bO Hjf PcQ CQSWhNS aj cJGHg bQjHG ef GKfj YTQ LRAG hCbd GdePchQ aj GdcJH GdeTghQI Cfg jfHZj Cf GdHYO Hjf Jbhje GdfjQjf CcKQ ef s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\30s
(3cTa GdXfhf (B2\1918s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs